A grounded theory of how social support influences physical activity in adolescent girls. Issue 1 (1st January 2018) - Laird, Yvonne; Fawkner, Samantha; Niven, Ailsa
ABSTRACT: Purpose : Adolescent girls are not sufficiently active to achieve health benefits. Social support from friends and family has been positively associated with physical activity in adolescent girls; however it is unclear how social support influences physical activity behaviour. This study aimed to develop a grounded theory of how social support influences physical activity in adolescent girls. Methods: A qualitative, constructivist grounded theory approach was adopted. Individual interviews explored adolescent girls' perspectives of how significant others' influenced their physical activity through providing social support, and through modelling physical activity. Results: Participants perceived social support to influence physical activity behaviour through performance improvements, self-efficacy, enjoyment, motivation and by enabling physical activity. Improvements in performance and self-efficacy were also linked to motivation to be active. Girls perceived modelling to influence behaviour through providing opportunities for them to be physically active, and by inspiring them to be active. Conclusion: The grounded theory outlines adolescent girls' perceptions of how significant others influence their physical activity and provides a framework for future research examining the role of social support on physical activity.